Pharmacology Knowledge Among Nurses Working in Nursing Homes in Norway: A Cross-Sectional Study - Siv Eriksen Taasen; Fred-Ivan Kvam; Kjersti Marie Blytt; El Houcine Messaoudi (SAGE Open Nursing)
Introduction The administration of drugs is an important part of nurses’ professional practice. A basic knowledge of pharmacological principles is required to make accurate decisions about drug management and conduct patient medication education. However, several studies have suggested that nurses have inadequate knowledge of pharmacology and medication management. Objective To explore the level of knowledge in pharmacology and medication management among nurses working in nursing homes (NHs). Methods We conducted a cross-sectional study at 24 NHs in Norway. The nurses took a multiple-choice test in pharmacology with 35 questions at their workplace. Each question had four alternative answers with one answer being correct. One point was awarded for a correct answer and zero for a wrong answer. The test included categories in general pharmacology, clinical pharmacology, and medication management. Results In total, 145 nurses completed the questionnaire. In the range of 0–35 correct responses, the mean score for the sum of all questions was 22.5, which equates to 66% of responses being correct. Linear multiple regression showed no association regarding gender, age distribution among the nurses, years since completing basic education in nursing, years of work experience in NHs, postgraduate education, and knowledge of pharmacology and medication management. Knowledge was better in the category medication management ( p  < 0.001) than in the category's general pharmacology and clinical pharmacology. When evaluating specific test questions, 38.9% of the nurses answered a question on opioids correct, 64.1% a question on anticoagulants correct, 33.5% knew the prerequisites for generic substitution, and 45.5% did not know the difference between agonists and antagonists. Conclusion Our results are in line with previous findings. The participating nurses working in the NHs have insufficient knowledge in pharmacology and medication management. This may cause harm and undermine patient safety.